Application of an Al-doped zinc oxide subcontact layer on vanadium-compensated 6H-SiC photoconductive switches - 周天宇 刘学超 黄维 代冲冲 郑燕青 施尔畏 (Chinese physics B, 2015)
Al-doped ZnO thin film （AZO） is used as a subcontact layer in 6H-SiC photoconductive semiconductor switches （PCSSs） to reduce the on-state resistance and optimize the device structure. Our photoconductive test shows that the onstate resistance of lateral PCSS with an n＋-AZO subcontact layer is 14.7% lower than that of PCSS without an n＋-AZO subcontact layer. This occurs because a heavy-doped AZO thin film can improve Ohmic contact properties, reduce contact resistance, and alleviate Joule heating. Combined with the high transparance characteristic at 532 nm of AZO film, vertical structural PCSS devices are designed and their structural superiority is discussed. This paper provides a feasible route for fabricating high performance SiC PCSS by using conductive and transparent ZnO-based materials.